Within-Person Longitudinal Associations Between Electronic Nicotine Delivery Systems Use and Smoking Cessation Efforts Among US Continuing Adult Cigarette Smokers. Issue 4 (10th November 2021) - Han, Dae-Hee; Lee, Shin Hyung; Seo, Dong-Chul
Abstract: Objectives: Prior studies that examined the role of electronic nicotine delivery systems (ENDS) use in smoking cessation have shown divergent conclusions. This study examined the time-course of ENDS-associated smoking abstinent behaviors among continuing cigarette smokers who were willing but unable to quit smoking. Methods: Data were drawn from the four waves of the Population Assessment of Tobacco and Health Study. Of the 1684 smokers who tried to quit smoking completely at Wave 1, a total of 1094 who were continuing smokers until Wave 4 and were not lost to follow-ups comprised the sample. Using generalized linear mixed modeling, we fitted weighted negative binomial regression models to examine within-person associations of ENDS use with quit attempts and number of days abstinent from smoking. Results: Quit attempt frequency and smoking abstinent days were highest at Wave 1, dropped at Wave 2, and then either increased a little or remained stagnant in later waves. ENDS use to quit smoking was associated with more frequent quit attempts (aIRR = 1.67, 95% CI = 1.42–1.95) and more abstinent days (aIRR = 3.28, 95% CI = 2.43–4.44), and the magnitude of such associations became stronger over time. ENDS use was associated with becoming a nondaily smoker among baseline daily smokers. Conclusions: ENDS use among continuing smokers may help increase the number of quit attempts and smoking abstinent days. Given that the study sample is continuing smokers who failed in complete smoking cessation, future research would be desirable that evaluates whether such abstinent behaviors sustain and manifest harm reduction with improved health outcomes. Implications: Smokers increasingly adopt electronic nicotine delivery systems (ENDS) to quit smoking. However, the association of ENDS use with smoking cessation efforts among continuing cigarette smokers who were willing but unable to quit smoking is largely unknown. This study found that quit attempts and smoking abstinent days increased with ENDS use to quit smoking by following up with population-representative continuing smokers. Additionally, this study assessed whether cigarette smokers' abstinent behaviors vary with their use of ENDS by estimating within-person associations with frequent assessments of both exposures and outcomes in a long-term perspective.